2007
DOI: 10.1071/fp07010
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-induced oxidative stress in coffee cell suspension cultures

Abstract: Selenium (Se) is an essential element for humans and animals that is required for key antioxidant reactions, but can be toxic at high concentrations. We have investigated the effect of Se in the form of selenite on coffee cell suspension cultures over a 12-day period. The antioxidant defence systems were induced in coffee cells grown in the presence of 0.05 and 0.5 mm sodium selenite (Na2SeO3). Lipid peroxidation and alterations in antioxidant enzymes were the main responses observed, including a severe reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 49 publications
0
53
0
8
Order By: Relevance
“…Increased ROS may also be formed directly from selenite and GSH in vitro (Saitoh and Imuran, 1987). Se treatment has been shown previously to induce ROS accumulation in Arabidopsis leaves and coffee (Coffea arabica) cells (Gomes-Junior et al, 2007;Tamaoki et al, 2008b). The production of ROS in the two Stanleya species was analyzed in situ using stains sensitive to superoxide and hydrogen peroxide.…”
Section: Effects Of Se On Leaf Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ROS may also be formed directly from selenite and GSH in vitro (Saitoh and Imuran, 1987). Se treatment has been shown previously to induce ROS accumulation in Arabidopsis leaves and coffee (Coffea arabica) cells (Gomes-Junior et al, 2007;Tamaoki et al, 2008b). The production of ROS in the two Stanleya species was analyzed in situ using stains sensitive to superoxide and hydrogen peroxide.…”
Section: Effects Of Se On Leaf Physiologymentioning
confidence: 99%
“…These two seleno-amino acids can be misincorporated into proteins, replacing Cys and Met, which causes Se toxicity Shrift, 1981, 1982;Stadtman, 1996). It has also been shown that Se causes reactive oxygen species (ROS) formation and oxidative stress in plants ( Gomes-Junior et al, 2007;Tamaoki et al, 2008b). Se toxicity in plants may directly result from the ROS generated via selenite reacting with reduced glutathione (GSH), as shown in vitro (Saitoh and Imuran, 1987).…”
mentioning
confidence: 99%
“…Under salt stress an accumulation of Asn (Ashraf and Harris 2004) and Gaba were observed (Bolarín et al 1995) Reactive oxygen species (ROS) are commonly produced in the cell and can act as signals in several transcription pathways, leading to altered patterns of gene expression which allow the plant to adjust adequately to the environment (Dutilleul et al 2003;Foyer and Noctor 2005a;2005b;Gratão et al 2005;Noctor 2006;Mhamdi et al 2010;Queval et al 2011). However, stress can result in an increase in ROS, causing the oxidation of lipids, proteins and DNA, thereby compromising the growth of the plant (Dutilleul et al 2003;Foyer and Noctor 2005a;Gratão et al 2005;Gomes-Júnior et al 2007). Some studies have indicated that Pro may act as a scavenger of ROS (Vicente et al 2004) and can stabilize membranes during salt stress (Hasegawa et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The nonspecific incorporation of selenoamino acids into proteins is thought to contribute to Se toxicity (Brown and Shrift, 1981). Alternatively, Se toxicity in plants could result from the formation of reactive oxygen species and oxidative stress (Gomes-Junior et al, 2007;Tamaoki et al, 2008).…”
mentioning
confidence: 99%